Macroglossia : A Case Report - Nataraja NP; Kumar PJ (Journal of All India Institute of Speech and Hearing, 1970)
This paper is a report  on  a  case of Macroglossia.The  articulatory behaviour  of a  boy of 14 years  with a congenital cystic swelling  occupying the  anterior 1/3  of the  tongue {approximately 50  c.c.) has been described.